Improving Reading Comprehension Using Contextual Teaching and Learning (CTL) - Yudha Aprizani (Studies in English Language and Education, 2016)
This study aimed to find out whether teaching-learning reading comprehension using Contextual Teaching and Learning (CTL) would get better results than using Direct Instruction approach. The research used a quantitative method. The population of the research was students from the Islamic University of Kalimantan Muhammad Arsyad Al-Banjari. The researcher used cluster random sampling to select two sample groups, the control group and the experimental group. The control group with 25 students was the class that continued to use the Direct Instruction approach. The experimental group, with 20 students, was the class tested using the CTL approach. The test was a written test with five multiple choice questions plus an essay test. The test was used to obtain the data. The students’ scores were the data for the study of reading comprehension comparing CTL and Direct Instruction. Based on the results of the study, the researcher found that CTL was more effective than Direct Instruction because the null hypothesis was rejected and the alternative hypothesis was accepted so that CTL was found to be better for teaching reading skills. CTL encourages materials that are related to the students’ surrounding so that it helps them use English related to their daily activities.